2011
DOI: 10.1073/pnas.1103027108
|View full text |Cite
|
Sign up to set email alerts
|

Tidal surge in the M2 proton channel, sensed by 2D IR spectroscopy

Abstract: The M2 proton channel from influenza A virus transmits protons across membranes via a narrow aqueous pore lined by water and a proton sensor, His37. Near the center of the membrane, a water cluster is stabilized by the carbonyl of Gly34 and His37, the properties of which are modulated by protonation of His37. At low pH (5-6), where M2 conducts protons, this region undergoes exchange processes on the microsecond to second timescale. Here, we use 2D IR to examine the instantaneous conformational distribution and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
147
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(154 citation statements)
references
References 49 publications
7
147
0
Order By: Relevance
“…As discussed above and in ref. 23, the water is more ice-like inside the channel in the Q2 state and exhibits slower orientational dynamics. Because a successful proton transfer event from one water molecule to the next requires collective rearrangement of the surrounding HB network (53,54), the slow dynamics of channel water inhibit PT.…”
Section: Significancementioning
confidence: 98%
See 1 more Smart Citation
“…As discussed above and in ref. 23, the water is more ice-like inside the channel in the Q2 state and exhibits slower orientational dynamics. Because a successful proton transfer event from one water molecule to the next requires collective rearrangement of the surrounding HB network (53,54), the slow dynamics of channel water inhibit PT.…”
Section: Significancementioning
confidence: 98%
“…The high-resolution crystal structure [Protein Data Bank (PDB) code 3LBW] crystallized at pH 6.5 revealed layers of well-ordered water clusters above the His37 tetrad (12). However, the water dynamics in the AM2 protein probed using 2D infrared (2D-IR) spectroscopy revealed that the well-ordered "ice-like" pore water dynamics at pH 8.0 change to more mobile and "liquid-like" dynamics (on the timescale of a few picoseconds) at pH 3.2 (23). This result suggests an interesting pH-dependent behavior of the AM2 protein that is highly relevant for understanding its PT mechanism.…”
mentioning
confidence: 99%
“…Moreover, linear infrared spectroscopy has significant limitations in revealing dynamics that are underscored by the vibrational lineshapes; for the M2 channel, these dynamical timescales are characteristic to water structures near the pore lining amides as has been demonstrated before. 31 Thus, the remainder of this work focuses on the 2D spectroscopy of the isotopically labeled amides.…”
Section: A Linear Ir Spectramentioning
confidence: 99%
“…When used in conjunction with isotope labeling, one can obtain residue-by-residue information on hydration dynamics, as has been demonstrated with experiment and theory over the past decade on several membrane protein domains, including CD3zeta, M2, and ovispirin. [29][30][31][32] In this study, we use a double mutant (D44N, R45A) 31,33,34 of the transmembrane domain of the M2 channel, with the pore lining carbonyls of its Ala30 and Gly34 residues isotopically labeled (i.e., 12 C= 16 O to 13 C= 18 O) to serve as site-specific IR probes. [35][36][37][38] The use of this double mutant avoids any potential complexity arising from the 2D IR signals of arginine and aspartic acid, which overlap with those of the 13 C= 18 O groups.…”
Section: Introductionmentioning
confidence: 99%
“…For an IR probe that is able to interact with water via H bonding, measurement of its FFCF can provide, sometimes in a site-specific manner, detailed information about the hydration dynamics of the protein molecule of interest. For example, this approach has been used to identify the existence of mobile water molecules inside Aβ40 amyloid fibrils (31,32) and to interrogate the water-assisted drug-binding mechanism of HIV-1 reverse transcriptase (33), among many other applications (34)(35)(36)(37)(38)(39). In the current study, we capitalize on the established sensitivity of the nitrile stretching vibration (C≡N) to local hydration and electrostatic environment (40) and use the unnatural amino acid p-cyano-phenyalanine (Phe CN ) as a local IR reporter.…”
mentioning
confidence: 99%